DERIVATION AND INFLECTION ON SELENA GOMEZ SONG LYRICS IN REVIVAL ALBUM - Halawa, Edarmawati (Research on English Language Education, 2021)
This study was designed by using descriptive qualitative method to analyze the data because it explains derivation and inflection affixes that found on Selena Gomez Song Lyrics in Revival Album. This study aimed to find out the derivation and inflection affixes on Selena Gomez song lyric in Revival Album also to describe the function ofeach derivation and inflection affixes found. The data was collected by using documentation. The result of this study there are two types of affix were used. They were prefix and suffix. There is no infix was used. Derivational prefix which is found–re. Meanwhile, derivational suffixes which are found, they are–ed,-ly,-ness,-tion,-ion,-cal.-ful,-er,-ity and -al. The functions of derivational affixes consist of noun forming, adverb forming, adjective forming, and verb forming. On the other hand inflectional suffixes consists of -s,-ing, -ed. The function of inflectional suffixes consist ofthird singular person marker, past tense marker, progressive marker, and plural marker.The mostly used of inflection affixes was suffix –ing functioned as progressive marker. Based on the finding, it is concluded that learn derivation and inflection affixes can helps learners create a new words by adding prefix and suffix. In conclusion, derivation affixes occur to create new word from existing word in two ways, they can change the meaning of word or the word class. And inflection affixes occur not to used to produce new words in the language, but rather to indicate aspects of the grammatical function of word.Thesuggestion fromresearcher to isto study moreaboutthederivation and inflection affixesnotonly fromthebookbutalsofromanother sourceslikesongs, moviesubtitle,etc.And suggests the English learner should learn derivation and inflection affixes because from this affixes can change the part of speech and also create a new meaning that can improve their vocabulary.